2010
DOI: 10.2174/157016110791330834
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Vascular Disease: Basic Concepts of Nitric Oxide Physiology, Endothelial Dysfunction, Oxidative Stress and Therapeutic Possibilities

Abstract: The vascular manifestations associated with diabetes mellitus (DM) result from the dysfunction of several vascular physiology components mainly involving the endothelium, vascular smooth muscle and platelets. It is also known that hyperglycemia-induced oxidative stress plays a role in the development of this dysfunction. This review considers the basic physiology of the endothelium, especially related to the synthesis and function of nitric oxide. We also discuss the pathophysiology of vascular disease associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 209 publications
1
34
0
Order By: Relevance
“…It is well-known that hyperglycemia-induced oxidative stress and inflammation play an important role in development of vascular endothelial dysfunction (5). Hyperglycemia stimulates the body to produce a large number of oxygen free radicals and then induces oxidative stress which damages vascular endothelial cells and causes DM vascular complications (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that hyperglycemia-induced oxidative stress and inflammation play an important role in development of vascular endothelial dysfunction (5). Hyperglycemia stimulates the body to produce a large number of oxygen free radicals and then induces oxidative stress which damages vascular endothelial cells and causes DM vascular complications (6).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, subjects with type 2 diabetes mellitus, which is characterized by insulin resistance, are at 2-to 4-fold increased risk of cardiovascular disease compared with those without diabetes (Kirpichnikov and Sowers, 2001). Vascular endothelial cells play a major role in maintaining cardiovascular homeostasis, and endothelial dysfunction is regarded as an important factor in the pathogenesis of diabetic vascular complications (Capellini et al, 2010). Insulin resistance is associated with endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) are produced by the non-enzymatic glycation and oxidation reactions of glucose or other reducing sugars with proteins, lipids and nucleotides. It had been suggested that AGEs trigger and aggravate the endothelium damage in diabetic complications (2). Previous evidence has linked AGEs with the development of atherosclerosis in diabetes, regardless of the diabetic status (3).…”
Section: Introductionmentioning
confidence: 99%